Building Students' Critical Thinking Skill through Problem-Based Learning Model - Paulus Haniko; Yenny Anggreini Sarumaha; Erwinsyah Satria; Nurmadina Hs; Anas (Widya Accarya, 2023)
Reality showed that one of the common problems being faced in the world of education at various levels of school is the low level of students' critical thinking skill. The low level of students' critical thinking skill is caused by the learning model applied in learning by the teacher being unable to stimulate students to improve their critical thinking skill. The purpose of this research was to build students' critical thinking skill through the implementation of a problem-based learning model. The method used in this research was a library research method or approach. The type of research used in this research was library research. Data collection in this research was carried out using documentation and literature study techniques, namely reviewing several journals, books, theses, scientific works sourced from the internet as a source of information that can be studied according to the theme of this research. The data obtained were then analyzed in depth to then be presented descriptively. The results of this research indicated that the implementation of problem-based learning model can build students' critical thinking skill. Because this learning model provides or bases problems as a starting point for students to investigate, inquire and solve. In this learning, students are gradually able to build concepts and principles from a material with their own abilities that integrate skills and knowledge that have been previously understood. Through this learning model students are active and have the opportunity to find and apply their own ideas in solving problems, thereby supporting students to develop their critical thinking skill.